Can ePROMs improve the understanding and management of lung cancer patients’ Quality of Life? A Scoping review (Preprint) - García Abejas, A (2023)
Background: Electronic patient-reported outcome measures (ePROMs) are essential for clinical practice and research. The growth of electronic health technologies has provided unprecedented opportunities to collect information systematically through ePROMs. They are widely used in scientific research, but we need more evidence if they will also be used, with their implementation, in daily clinical practice. For example, patients with lung cancer have an advanced stage of the disease when diagnosed. This entails tremendous suffering due to high mortality and losses in the different dimensions of the human being. In this case, monitoring symptoms and other outcomes expressly represent great utility in improving a patient's quality of life. Objective: ePROMs provided unprecedented opportunities to collect information systematically. The authors aim to prove that ePROMs are more helpful in managing patient symptoms, lung cancer, and overall survival than their alternatives, such as non-electronic PROMs. Methods: This scoping review considered articles published between 2017 and 2022 identified through searches in PubMed, Scopus, Cochrane, CINAHL, and PsycINFO. We found 5,097 articles; after eliminating duplicates, we reduced them to 3,315, and after reading the abstract, we were left with 56; finally, after applying the exclusion criteria, we reviewed 12. Arksey and O'Malley's five-step framework was used to refine the initial search results with the following research questions: 1) Do ePROMs help physician-patient communication? 2) To what extent do they improve decision-making? 3) Are institutions and their digitization policies barriers or enablers for this process? 4) What else is needed for routine implementation?. Results: Twelve articles were included in this review. The answers to our questions were: 1) ePROMs are an integrative and facilitative communication tool, highlighting their importance in the relationship between palliative care and medical oncology. 2) ePROMs help assess patient symptoms and functionality more accurately and facilitate clinical decision-making. In addition, it allows more precise predictions of overall patient survival and the adverse effects of their treatments. 3) The main institutional obstacles are the initial investment, which can be costly, and the data protection policy. However, as enablers, we have better funding through the development of telemedicine, support from institutional leaders to overcome resistance to change, and transparent policies to ensure the safe and secure use of ePROMs. 4) More than evidence for its routine application, its implementation must overcome physicians' inertia and safeguard the confidentiality of the data obtained. Conclusions: Routine collection of remote ePROMs is an effective and valuable strategy for providing real-time clinical feedback. In addition, it provides satisfaction to patients and professionals. Optimizing ePROMs in lung cancer patients leads to a more accurate view of health outcomes and ensures quality patient follow-up. It also allows us to stratify patients based on their morbidity, creating specific follow-ups for their needs. However, data privacy and security are concerns when using ePROMs to ensure compliance with local entities. At least four barriers were identified: cost, complex programming within health systems, security, and socio-health literacy.